The Impact of Social Awareness and Lifestyles on Household Carbon Emissions in China - Li, Jun; Zhang, Dayong; Su, Bin (Ecological economics, 2019)
Household carbon emissions account for a significant proportion of the national total emissions. Using a unique nation-wide survey data, this paper investigates the impact of different subjective measures of social awareness on household carbon emissions in China. Subjective variables are found to have significant impacts on household carbon emissions. Feeling secure, compliance with rules, and happiness have negative and significant effects on household carbon emissions, whereas the impact of interest in social issues is positive, which indicates the existence of a gap between awareness and behavior. The impacts of consumer lifestyles on the relationship between awareness and household emissions are also explored and are found to play a significant role in the relationship between awareness and emissions. People with a frugal lifestyle not only associate with lower emissions but also reinforce the role of social awareness. Furthermore, substantial differences are found across rural/urban areas and regional and income groups in China. The government should further promote a green lifestyle and give households more incentives to engage in green consumption behavior. •Household emissions are studied based on China Household Finance Survey.•Subjective factors are found to have significant impacts on household emissions.•Lifestyles matter in the relationship between awareness and household emissions.•Regional and income differences are considered in the analysis.